Special Ops : Lioness. Season one. [videorecording (DVD)] - Sheridan, Taylor (Paramount, 2024)
Inspired by an actual US Military program, follows the life of Joe while she attempts to balance her personal and professional life as the tip of the CIA's spear in the war on terror. The Lioness Program, overseen by Kaitlyn Meade and Donald Westfield, enlists an aggressive Marine Raider named Cruz to operate undercover alongside Joe among the power brokers of State terrorism in the CIA's efforts to thwart the next 9/11.